The immunohistochemical expression Ki-67 In Polymorphous Low Grade Adenocarcinoma of the Salivary Glands (Mustansiria Dental Journal, 2024)
Background: Polymorphous Low Grade Adenocarcinoma is a rare malignant tumor of minor salivary glands. It has an unique histopathological, clinical and behavioural features. Most of its incidence has been presented in the palate. It shows a variety of growth patterns within the same one lesion, including cribriform, tubular, and solid areas that may mimic adenoid cystic carcinoma. The tumor cells histologically are characterized by lacking of nuclear atypical and hyperchromatism with rare mitoses. However, the prognosis of this tumor is good because of its low grade, although it has an unpredictable potential to metastasize.Objectives: To evaluate the histopathological expression of Ki-67 proliferation antigen in Polymorphous low grade adenocarcinoma and compare the results with the clinicopathological parameters and grading of the tumors.Materials and Methods: This study includes 20 cases with Polymorphous Low Grade Adenocarcinoma of minor salivary glands diagnosed histopathologically and treated surgically, were investigated for the immunohistochemical expression of Ki-67 antigen. Immunohistochemical staining was performed using a Labeled Strept- Avidin Biotin method (LSAB) and 0.05 (two-sided) was the level of significance.Results: Twenty cases of Polymorphous Low Grade Adenocarcinoma of salivary glands were histologically diagnosed in this retrospective study to evaluate the expression of Ki-67. The mean age for patients with PLGA was nearly (50.6). (12) (60%) cases were males and (8) (40%) cases were females and also male to female ratio was (1.5:1).In regarding to site distribution, the most common site was the palate followed by the submandibular gland and floor of the mouth. Conclusions: it was observed that there is a higher rate of cellular proliferation in malignant tumors with high grade, indicating their role in the malignancy and aggressive behavior of these tumors.